PERBUATAN MELAWAN HUKUM DALAM PERJANJIAN KERJA DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA - Nugroho, Dimas (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
The covid-19 pandemic has caused PT. Bintang Inti Karya experienced a decrease in income, so the company made a unilateral salary deduction for workers because they were unable to pay workers' salaries as usual. The existence of unilateral salary deductions causes rights disputes between employers and workers. This study uses a normative research method with a statutory and conceptual approach. The results showed that the work agreement at PT. Bintang Inti Karya which is actually a standard agreement, substantially there are still several weaknesses that make the work agreement less than ideal to be used as a basis for carrying out work relations, especially related to dispute resolution. In addition, the work agreement is not in accordance with the principle of freedom of contract because the making of the work agreement does not involve the workers in determining the contents of the agreement. Unilateral salary deductions based on Article 1365 of the Civil Code can be categorized as a form of unlawful act, where the act is not in accordance with the principles of the agreement, namely the principles of pacta sunt servanda, good faith, balance and propriety. Departing from these problems, it is necessary to construct an ideal work agreement as the basis for carrying out an employment relationship. All provisions regarding the rights and obligations of the parties in an employment relationship must be clearly and completely contained in the employment agreement. In addition to referring to the terms and conditions contained in Article 55 paragraph (1) of the Labour Act, a work agreement must contain provisions related to force majeure as well as the mechanism and legal domicile of dispute resolution in order to realize the construction of an ideal work agreement. Keywords: Employment Agreement, Unlawful Acts, Construction.